Promoting Women's Rights by Indigenous Means : An Innovative Project in Kenya - Chopra, Tanja (World Bank, Washington, DC, 2018)
The World Bank's Justice for the Poor (J4P) program seeks to gain a deeper understanding of local level justice processes, in order to identify pragmatic ways to allow access to justice for the poor and marginalized. Reform programs in all sectors often ignore the value systems, social structures and realities of the local communities they address, therefore delivering mixed results. Further innovative programs are required to foster meaningful connections between local social structures and value systems and official justice institutions. The key to success will be the ability of different systems to adapt. Interventions may adjust the official system to local realities, but another possible focus is on the transformation of cultural values of individual communities. Processes of transformation allow change to be set in motion from within a society itself. This can mean that positive values are emphasized and re-instated where lost or negative values are transformed into positive ones. The effect is that state institutions can gain legitimacy in the eyes of local communities, and official rights are promoted. Learning from Kenya National Human Rights Commission (KNHRC's) project and similarly innovative interventions, J4P research will focus on socio-cultural values, in order to develop spaces for local debates over values and in order to determine the appropriate agents for change at the local level.